PENGARUH PEMAHAMAN WAJIB PAJAK, PELAYANAN PETUGAS PAJAK, KESADARAN WAJIB PAJAK, DAN TINGKAT PENDIDIKAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM - Rinny Meidiyustiani; Qodariah Qodariah; Sekar Sari (Jurnal Bina Akuntansi, 2022)
This study aims to analyze the effect of understanding taxpayers, tax officer services, taxpayer awareness, and education levels on taxpayer compliance. This research uses primary data. The population in this study is the taxpayer of SMEs in the food and beverage sector in South Tangerang City by using accidental sampling techniques by distributing questionnaires of 100 respondents. The data analysis technique used in this study is the method of multiple linear regression analysis and is processed using SPSS version 26. The results of this analysis show that understanding taxpayers, tax officer services, and education levels have a positive and significant effect on taxpayer compliance while awareness of taxpayers no significant effect on taxpayer compliance. While the remaining 44.7%, influenced by other variables outside the research model.